A comparison of noninvasive and invasive acupuncture in preventing postoperative nausea and vomiting: A protocol for systematic review and Bayesian network meta-analysis. Issue 31 (31st July 2020) - Fu, Cheng-Wei; Shu, Qing; Jiao, Yang; Wu, Tong; Song, Ai-Qun; Zhu, Qiao-Chu; Zhang, Wei-Ping
Abstract: Background: Postoperative nausea and vomiting (PONV) is a main complication of surgery, and by now, drugs cannot prevent it completely. Some meta-analyses have proved acupuncture therapy can prevent PONV. However, it is still controversial whether noninvasive acupuncture therapies are comparable with invasive ones. This study uses Bayesian network meta-analysis to compare the effectiveness of different forms of acupuncture in preventing PONV. Methods: PubMed/Medline, Cochrane library, Web of Science, Ebsco, Ovid/Embase, China National Knowledge Infrastructure, Wanfang Database, VIP Database, and China Biology Medicine disc will be searched from inception to May 2020. All randomized control trails meet the criterion will be included. Quality evaluation of included studies will be implemented with Cochrane risk-of-bias tool. STATA 14.0 will be used to perform pairwise meta-analysis. Addis 1.16.8, R 3.6.3, OpenBUGS 3.2.3, and STATA 14.0 will be used to conduct network meta-analysis. The evidence will be assessed by the grading of recommendations assessment, development, and evaluation approach using GRADE Profiler 3.6. Results: The results of this review will be submitted to a peer-reviewed journal for publication and generate a comprehensive review of current evidence. Conclusion: Our results will help to improve the clinical decision-making ability and policy-making in PONV domain. Systematic review registration: The protocol has been registered on INPLASY 202060108. Abstract : Supplemental Digital Content is available in the text